2014
DOI: 10.1039/c4ee01580k
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of minority-carrier diffusion lengths using wedge-shaped semiconductor photoelectrodes

Abstract: Measurement of the photocurrent as a function of the thickness of a light absorber has been shown herein both theoretically and experimentally to provide a method for determination of the minority-carrier diffusion length of a sample. To perform the measurement, an illuminated spot of photons with an energy well above the band gap of the material was scanned along the thickness gradient of a wedgeshaped, rear-illuminated semiconducting light absorber. Photogenerated majority carriers were collected through a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 23 publications
4
45
0
Order By: Relevance
“…† The sharp decay in f(z) agrees well with expectations for diffusion-limited photocurrent, in which the concentration of minority carriers decays with distance from the space charge region. 24,[35][36][37][38][39][40] From Fig. 2(b), it can be seen that the vast majority of the collected carriers are those generated within the first 10 nm of the surface of the electrode, which is in good agreement with our prior work, in which the collection length was determined to be approximately 20-40 nm by analysis of film thickness-dependent photocurrents.…”
Section: This Journal Is © the Royal Society Of Chemistry 2018supporting
confidence: 86%
See 1 more Smart Citation
“…† The sharp decay in f(z) agrees well with expectations for diffusion-limited photocurrent, in which the concentration of minority carriers decays with distance from the space charge region. 24,[35][36][37][38][39][40] From Fig. 2(b), it can be seen that the vast majority of the collected carriers are those generated within the first 10 nm of the surface of the electrode, which is in good agreement with our prior work, in which the collection length was determined to be approximately 20-40 nm by analysis of film thickness-dependent photocurrents.…”
Section: This Journal Is © the Royal Society Of Chemistry 2018supporting
confidence: 86%
“…[20][21][22][23], requires fabrication of full device stacks that are measured under vacuum, which prohibits use of this method for characterization of photoelectrochemical systems under real operating conditions. To overcome this characterization gap and extract the diffusion length, Pala et al 24 suggested measuring photocurrent changes in wedge-shaped thin films. However, such geometries are difficult to fabricate and their behavior may deviate significantly from the performance of planar structures.…”
Section: Introductionmentioning
confidence: 99%
“…Another somewhat innovative approach was recently reported by Pala et al using wedge-shaped semiconductor photoelectrodes. 25 They showed that for a sample with a thickness (w) much larger than w d , the photocurrent (J) is approximated as a constant factor multiplied by the reciprocal exponential of w/L D (i.e., J p exp(Àw/L D )). Using a wedge-shaped semiconductor photoelectrode deposited on a transparent substrate ( Fig.…”
Section: Charge Carrier Dynamicsmentioning
confidence: 99%
“…Compared with the state-of-art nanoporous photoelectrodes, the PEC performance obtained by the BiVO 4 NW arrays is significantly lower. Some studies indicated that reducing BiVO 4 nanosize to be below its hole diffusion length would significantly enhance electron-hole separation [368,369]. Therefore, reducing the diameter of BiVO 4 NWs is important to achieve high PEC performance.…”
Section: Nanowire-based Arraysmentioning
confidence: 99%